1994
DOI: 10.1002/j.1552-4604.1994.tb02002.x
|View full text |Cite
|
Sign up to set email alerts
|

A Placebo‐Controlled Evaluation of Single, Escalating Doses of CL 284,846, a Non‐Benzodiazepine Hypnotic

Abstract: This report describes the first evaluation in humans of CL 284,846, a non-benzodiazepine compound with a preclinical profile indicative of sedative/hypnotic properties. Healthy, normal male volunteers were assigned randomly to receive single oral doses of 1, 5, 15, 30, or 60 mg of CL 284,846 or placebo on a double-blind basis. Observations were made over the subsequent 25 hours to determine the safety, pharmacokinetic profile, and psychometric effects of the test compound. CL 284,846 was well tolerated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 15 publications
2
43
0
Order By: Relevance
“…Zaleplon's t 1/2 was approximately 1 h following both oral and iv administration. The pharmacokinetic results observed for zaleplon following oral administration in the present study are similar to those observed previously [3].…”
Section: Zaleplon Pharmacokineticssupporting
confidence: 94%
See 2 more Smart Citations
“…Zaleplon's t 1/2 was approximately 1 h following both oral and iv administration. The pharmacokinetic results observed for zaleplon following oral administration in the present study are similar to those observed previously [3].…”
Section: Zaleplon Pharmacokineticssupporting
confidence: 94%
“…Plasma samples were assayed for determination of zaleplon concentrations by a validated high performance liquid chromatography method with fluorescence detection [3]. Standard curves were linear over the zaleplon plasma concentration range of 0.55-300 ng/mL, with a sensitivity of 0.5 ng/mL.…”
Section: Sample Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is suggested that the hypnotic effect of zaleplon is characterized by rapid onset, as compared with that of triazolam and the other hypnotics tested. Elimination of zaleplon in rats was rapid with a terminal half-life of approximately 1 h, and absorption was rapid, similar to what has been observed in humans (5,9). Thus, the EEG recording and spectral analysis study in rats support the pharmacokinetics characterized by rapid absorption of zaleplon, and the rapid sleep onset of zaleplon may be solely due to rapid absorption.…”
Section: Discussionsupporting
confidence: 79%
“…The elimination half-life of zaleplon is approximately 1 h, regardless of dose and the absorption is rapid (9). Therefore, as the hypnotic action of zaleplon can be characterized by rapid onset and short duration of action, it has been suggested that zaleplon should be classified as an ultra-short-acting sedative / hypnotic agent, and it may be used for insomnia in patients whose main difficulty is in falling asleep.…”
Section: Introductionmentioning
confidence: 99%